Influence of teacher characteristics on teacher use of test blueprint at the basic schools in Cape Coast Metropolis - Andam, Ivan Cliff (University of Cape Coast, 2023)
The study sought to explore the influence of teacher characteristics on teacher use of test blueprint at the basic schools in cape coast metropolis. The descriptive survey design was employed to carry out the study. Three hundred teachers out of the total population of 1,244 teachers in the 79 public Junior High Schools in Cape Coast Metropolis were considered. A purposive sampling technique was employed in the sampling procedures. A self developed five-point likert scale questionnaire was used in collecting the data for the study. Frequencies, percentages, means, standard deviations, independent sample T-test, One-Way Analysis of Variance (ANOVA) and Simple Linear Regression were used to analyse the data. The results revealed that teachers are highly experienced in using test blueprint to construct test items. The results also showed that there is a moderate level of anxiety among teachers regarding the use of test blueprints in constructing test items. The results further revealed that there was no statistically significant gender difference in teachers‟ use of test blueprint. The results further revealed that perceived usefulness significantly influenced teachers‟ use of test blueprints in test item construction. The study recommended that teachers should participate in continuous professional development workshops that focus on enhancing their skills in using test blueprints effectively. These workshops should provide hands-on training to address areas of uncertainty or anxiety about test construction, ensuring that teachers are both confident and competent in their use of test blueprint. The focus should be on practical applications, common challenges, and innovative ways to integrate test blueprints into everyday assessment practices.
xiv, 167p:,ill.
Keywords: Table of specification; Test item construction; Test blueprint; Teachers experiences; Teachers attitudes; Teacher characteristics